Measuring Changes of Students Conceptual Understanding of Literacy and Numeracy in Natural Science by Using Rasch Model - Ghullam Hamdu; Deni Hadiana; Novi Sylvia; Icha Apipatunnisa; Ade Yulianto (Universitas Pendidikan Ganesha, 2023)
The low literacy and numeracy abilities of Indonesian students based on the PISA encourage assessment policies based on literacy and numeracy. This study aims to analyze the feasibility of the items developed and changes in students' understanding of concepts after implementing literacy and numeracy-based learning processes on science subject matter topics related to education for sustainable development. The research method used in this research is the one-group pretest-posttest-design experimental method. Concerning the one-group pretest-posttest-design experimental method, the sample in this study was one whole class. Data was collected through a test instrument for students' conceptual understanding of science subjects. Raw data from students' grades were processed using the Rasch Model analysis. Through Rasch's analysis, the pattern of changes in students' conceptual understanding abilities was identified by comparing the response patterns of problem difficulty and students' abilities. The research results show that the items developed in the test instrument are appropriate for measuring students' abilities. Literacy and numeracy-based learning can improve students' understanding of concepts. Seven out of 53 students were identified as having decreased abilities. Student misconceptions cause it, the types of questions developed, student internal factors, and the teaching materials used. This analysis estimates the effectiveness of educational innovations and student ability in detail.